Identification Of Diseases In Rice Plant Using Chatbot With Methode Artificial Intelligence Markup Language and Normalization - Erwin Apriliyanto; Kusrini Kusrini; Rudyanto Arief (RESEARCH : Journal of Computer, Information System & Technology Management, 2020)
Information Services in agriculture are entering the era of industrial revolution 4.0, always associated with the use of automation machines integrated with the internet network. The technological sophistication of this era makes many conditions change. The chatbot application is one of the right solutions to solve farmer problems, this farmer chatbot application is about the information on handling rice plants, and this application uses the Artificial Intelligence Markup (AIML) method. The purpose of this study was to test the accuracy of the answers to the chatbot. This research method uses question data with words under 5 words and above 5 words, and uses question data according to keywords and outside keywords in this chatbot, with 50 question data, with each question data tested four times than taken the average. average. The results of this study are to get an accuracy of 90.9%, while the response time for answering questions of less than 5 words is 0.01 seconds, and for more than 5 words is 0.02 seconds with a data set of 1000 lines.